2020
DOI: 10.2174/1567202616666191029112334
|View full text |Cite
|
Sign up to set email alerts
|

Association of Common Variants in the IL-33/ST2 Axis with Ischemic Stroke

Abstract: Background: Recent studies have reported that the levels of serum interleukin-33 (IL- 33) and its receptor, suppression of tumorigenicity 2 (ST2), are potential biomarkers for susceptibility of cardiovascular diseases. However, the genetic association of the IL-33/ST2 axis with cardiovascular diseases remains controversial. Objective: We aimed to investigate the association between common variants in the IL-33/ST2 axis and ischemic stroke in the Han Chinese population. Methods: We consecutively enrolled 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Although, several other polymorphisms within the IL-33 gene have been shown to be significantly associated with asthma susceptibility in various populations (50). A significant relationship was also found between the IL-33 rs7044343 polymorphism and ischemic stroke in a Chinese cohort (67). On the contrary, there were no associations between the IL-33 rs7044343 polymorphism and inflammatory bowel disease or idiopathic achalasia in an Italian cohort (68,69).…”
Section: Discussionmentioning
confidence: 92%
“…Although, several other polymorphisms within the IL-33 gene have been shown to be significantly associated with asthma susceptibility in various populations (50). A significant relationship was also found between the IL-33 rs7044343 polymorphism and ischemic stroke in a Chinese cohort (67). On the contrary, there were no associations between the IL-33 rs7044343 polymorphism and inflammatory bowel disease or idiopathic achalasia in an Italian cohort (68,69).…”
Section: Discussionmentioning
confidence: 92%
“…The involvement of IL-33 in the course of ischemic stroke has been widely reported. The study of Li et al pointed out that there is a correlation between the common variants of IL-33 and the reduced risk of ischemic stroke in the Chinese Han population [36]. Similarly, Li and his colleagues found that IL-33 improves ischemic brain injury by promoting Th2 response and inhibiting Th17 response [36].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Li et al pointed out that there is a correlation between the common variants of IL-33 and the reduced risk of ischemic stroke in the Chinese Han population [36]. Similarly, Li and his colleagues found that IL-33 improves ischemic brain injury by promoting Th2 response and inhibiting Th17 response [36]. Interestingly, earlier studies pointed out that IL-33 could attenuate the occurrence and development of atherosclerosis by inducing IL-5 and ox-LDL antibodies [37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that did not meet these standards were excluded. Thus, seven casecontrol studies met our inclusion criteria for qualitative data analysis, and contained a total of 10686 cases and 10775 healthy subjects (7,8,(37)(38)(39)(40)(41). Two researchers simultaneously screened the studies back-to-back and obtained consistent results.…”
Section: Study Characteristicsmentioning
confidence: 99%